Curriculum and Student’s Results Analysis Based on Cerebral Hemisphere Functions Using Association Rule - Yang, Xang; MEKTHANAVANH, Vinath; CHONGXIONGCHA, Ueyang; SOUKCHALEUN , Xaysavath; SAYCOCIE, Souphilack (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This paper presents the usage of data mining techniques with association rules to analyze students’ grades and curriculum based on Cerebral Hemisphere functions. The goal of this investigation was to analyze the relationships between student learning outcomes for each subject grouped in the content of the left brain and the right brain. The information used for decision support to develop the scholarly educational programs is the grades of students from two curriculums there are four and five years of study program. Two batches of students from Souphanouvong University, Lao PDR are utilized in this study. Clustering techniques are applied to students’ grades and subjects. Students’ grades are divided into 3 types “Good”, “Fair”, “Poor” and subjects are divided into 2 clusters “Left Hemisphere”, “Right Hemisphere”. The association rule technique is deployed to demonstrate the relationship between students’ grades and balancing of subjects in the curriculum based on Cerebral Hemisphere functions. The study results show that demonstrated the improvement of students’ grades from both generations have similar pattern in the academic year that the subjects of left hemisphere is balanced with the subjects of right hemisphere. Moreover, the concept of this paper can apply to learning modules and assist improving the curriculum in some academic years.